Factors Affecting the Outcome of Extracorporeal Shockwave Lithotripsy in Urinary Stone Treatment - Nisar Ahmad, Shah Jahan Ur Rehman, Khalid Khan, Majed Saeed, Saqlain Amjad, Ajmal Rasheed, Ussama Iftikhar (Pakistan Journal of Medical & Health Sciences, 2023)
Background and aim: The recurrence of urinary stones occurs in two thirds of patients within a 20-year period, making urinary stones a common pathology. Among urology pathologies, kidney stones rank third behind urinary infections and conditions of the prostate. The present study intended to assess various factors affecting the extracorporeal shockwave lithotripsy (ESWL) outcome in urinary stone treatment. Methods: This cross-sectional study was carried out on 136 urinary stone patients who underwent extracorporeal shockwave lithotripsy in the Department of Urology, Sahiwal Teaching Hospital, Sahiwal for the duration from September 2021 to August 2022. Computed tomography confirmed the presence of stones and measured the size (3-20 mm), distance from skin to stone, location, and density in Hounsfield units. Patient’s characteristics such as estimated rate of glomerular filtration and BMI were measured. A successful ESWL requires at least a 3mm residual renal stone fragment in post-therapy, and at least a complete clearance of ureteric stones at the end of treatment. SPSS version 26 was used for descriptive statistic. Results: Of the total 136 urinary stone patients, there were 108 (79.4%) male and 28 (20.6%) females. The incidence of stones present in proximal ureter, mid, and distal ureter was 72 (52.9%), 7 (5.1%), and 57 (41.9%) respectively. All the patients underwent ESWL 1.5 times (average), and the success rate in first, second, and third session was 67.8% (n=92), 83.8% (n=114), and 91.2% (n=124) respectively. The overall success rate of ESWL was 80.9%. A multivariate analysis revealed that HU [OR=0.89, 95% CI, 0.96-0.98, P=0.001) and stone size [OR=0.79, 95% CI, 0.62-0.98, P=0.051] were significantly affecting the first ESWL session success rate. Third session success rate was significantly affected by stone size [OR=0.76, 95% CI, 0.58-0.95, P=0.015]. Stent associated higher failure rate [OR=6.425, 95% CI, 2.132-18.235, p=0.001] and ESWL failure was three-times higher in females than in male. Conclusion: The present study found that the overall success rate of ESWL in urinary stone treatment was 80.9%. ESWL success rates were affected by stone size and HU. Patients’ pain and fragmentation levels should be considered when adjusting the intensity of ESWL. Keywords: Urinary stone treatment, Outcomes, Extracorporeal shockwave lithotripsy